(untitled) (Research, Society and Development, 2021)
Tannins from Myrcia splendens from the Amazon rainforest were used for the first time in the formulation of a urea-tannin-formaldehyde (UTF) resin. The objective was to evaluate the effect of different tannin proportions on the glue line performance in Pinus sp. woods, glued with UTF adhesive. The tannins were extracted in a water bath, using 1500 mL of water and 100g of dry bark (liquor/bark 15:1), with addition of 3% Na2SO3, at a temperature of 70 °C for three hours. The adhesives formulations were based on the gradual replacement of mass of the urea-formaldehyde (UF) adhesive by tannin powder, totalizing four compositions and one control treatment. UTF adhesives were evaluated for their physicochemical properties, shear bond strength (wet and dry) and wood failure. The addition of M. splendens tannins to the urea formaldehyde adhesive promoted an increase in glue line strength. The proportion of 5.0% of tannins proved to be ideal in the formulation of the UTF adhesive, considering all the parameters evaluated. Thus, this study proves the potential use of Amazonian tannins from Myrcia splendens in the partial composition of more sustainable UTF adhesives.